2019
DOI: 10.1007/978-3-030-10752-9_12
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Drones in Ambient Assisted Living Systems for the Elderly

Abstract: Following years of restricted military applications, recently unmanned aerial vehicles (UAV) also known as drones have become the new disruptive force in many industrial and everyday life applications. Very obvious usage areas are transportation and parcel delivery. However, recent research reveals that there are a number of ways that drones can be employed to help elderly people sustain a better independent lifestyle. This paper introduces some of the most recent and interesting applications that drones can f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…In this respect, we could highlight a project for a custom-made quadcopter for monitoring patients indoors using images, sonar and voice recognition techniques [ 25 ]. A recent paper has introduced some of the most recent and interesting applications that drones can find in creating ambient assisted living environments for the elderly [ 26 ]. Even, a framework has been proposed for UAV navigation and people/object detection in cluttered indoor environments.…”
Section: General Description Of the Systemmentioning
confidence: 99%
“…In this respect, we could highlight a project for a custom-made quadcopter for monitoring patients indoors using images, sonar and voice recognition techniques [ 25 ]. A recent paper has introduced some of the most recent and interesting applications that drones can find in creating ambient assisted living environments for the elderly [ 26 ]. Even, a framework has been proposed for UAV navigation and people/object detection in cluttered indoor environments.…”
Section: General Description Of the Systemmentioning
confidence: 99%
“…As per Radosveta Sokullu [1], In his paper discussed that the drone is equipped with many components for flying. These Components are generalized into 5 categories and the block diagram is as shown in Fig.…”
Section: A General Components In a Dronementioning
confidence: 99%
“…Based on [1], Drones are classified based on capability of flight and configuration or structure. As Shown in Fig.…”
Section: B Drones Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances have shown that small drones with special arms can be used to bring medicines, take hold of a glass of water, pick up spectacles from the table or even sort clothes. [ 12 ] Thanks to UAV technology, now, automated external defibrillators can reach to the patients in no time to provide rapid emergency interventions. [ 13 14 ] In this way, UAVs can be used for both acute and chronic health conditions and improve health services delivery in noninstitutional settings.…”
Section: Introductionmentioning
confidence: 99%